What Does it Mean to Have a Right? - Dieter Birnbacher (Intergenerational Justice Review)
This contribution offers an introduction into the language of rights and the role rights play in ethics and law, with special reference to the rights of children. It emerges that there are a number of very different functions characteristic of 'rights talk', both in ethics and law, and that many of them offer opportunities for strengthening appeals to moral and legal principles while others involve pitfalls that should be avoided. In conclusion, two of the theoretical questions raised by rights are addressed: whether the concept of rights can be replaced without loss by the concept of obligation, and whether rights should be seen as social constructs derived from obligations, or whether it is more plausible to reverse the order of priority.